Effectiveness of Positive Psychology Intervention on Depression and Quality of Life of Post-Stroke Depressed Patients - Mikaili Baghi, Niloofar; Abdollahzadeh, Marzieh; Samadifard, Nasim; Mollaei, Samira; Yekta, Mohammad Reza (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The objective of the present study was to examine the effectiveness of Positive Psychology Intervention (PPI) in reducing depressive symptoms and enhancing the quality of life in patients with PSD. Methods and Materials: The present study utilized a quasi-experimental design with a pretest-posttest structure and a control group. The study population consisted of individuals diagnosed with post-stroke depression who attended psychotherapy clinics in Tehran in 2024. A sample of 30 patients with major depressive disorder (MDD) following a stroke was selected using convenience sampling and randomly assigned to either an intervention or control group. Following baseline assessments of depression and quality of life, participants in the intervention group received eight sessions of group-based Positive Psychology Intervention. Post-intervention assessments were conducted using the Beck Depression Inventory-II (BDI-II; Beck et al., 1996) and the Stroke-Specific Quality of Life Scale (SS-QOL; Williams et al., 1999). Data were analyzed using Analysis of Covariance (ANCOVA) in SPSS-26. Findings: The results of one-way covariance analysis indicated that the intervention had a significant effect on depression (F = 86.33, p < .05) and quality of life (F = 65.47, p < .05). The effect of the covariate variable (pretest scores) was not significant (p > .05) for either depression or quality of life posttests. Conclusion: The findings from this study underscore the effectiveness of Positive Psychology Intervention in reducing depressive symptoms and improving quality of life among patients with post-stroke depression. The results highlight the importance of incorporating positive psychological activities as a strategy to enhance the well-being of individuals affected by PSD.